Impact of Serum Lactate as an Early Serum Biomarker for Cardiopulmonary Parameters within the First 24 Hours of Intensive Care Unit Treatment in Patients with Isolated Traumatic Brain Injury - Bender, Michael; Friedrich, Michaela; Voigtmann, Hans; Haferkorn, Kristin; Uhl, Eberhard; Stein, Marco; Justus Liebig University Giessen (My University, 2023)
Objective: Cardiopulmonary (CP) complications are well-known phenomena in patients with isolated traumatic brain injury (iTBI) that can lead to tissue hypoperfusion and hypoxia. Serum lactate level is a well-known biomarker, indicating these systemic dysregulations in various diseases, but this has not been investigated in iTBI patients so far. The current study evaluates the association between serum lactate levels upon admission and CP parameters within the first 24 h of intensive care unit (ICU) treatment in iTBI patients. Patients and Methods: 182 patients with iTBI who were admitted to our neurosurgical ICU between December 2014 and December 2016 were retrospectively evaluated. Serum lactate levels on admission, demographic, medical, and radiological data upon admission, as well as several CP parameters within the first 24 h of ICU treatment, were analyzed, as well as the functional outcome at discharge. The total study population was dichotomized into patients with an elevated serum lactate level (lactate-positive) and patients with a low serum lactate level (lactate-negative) upon admission. Results: 69 patients (37.9%) had an elevated serum lactate level upon admission, which was significantly associated with a lower Glasgow Coma Scale score (p = 0.04), a higher head AIS score (p = 0.03), and a higher Acute Physiology and Chronic Health Evaluation II score (p = 0.01) upon admission, as well as a higher modified Rankin Scale score (p = 0.002) and a lower Glasgow Outcome Scale score (p < 0.0001) at discharge. Furthermore, the lactate-positive group required a significantly higher norepinephrine application rate (NAR; p = 0.04) and a higher fraction of inspired oxygen (FiO2; p = 0.04) to maintain the defined CP parameters within the first 24 h. Conclusion: ICU-admitted iTBI patients with elevated serum lactate levels upon admission required higher CP support within the first 24 h of ICU treatment after iTBI. Serum lactate may be a helpful biomarker for improving ICU treatment in the early stages.
Keywords: serum lactate; traumatic brain injury; cardiopulmonary parameters; intensive care unit treatment; ddc:610